Let's Party! - "Stine, Megan" (Harper Collins Promotion: China, 1998)
Ashley has a great idea! She's going to give a surprise party for her friend Jennifer. But Ashley gets a surprise, too -- when she finds out that Mary-Kate is giving another party for her best friend Amanda on the same night! But the biggest shocker of all is the one Dad has for both of the girls- one that will change their lives big-time!
Keywords: Twins Fiction